Principles of Neuropsychological Rehabilitation. - Prigatano, George P. (Oxford University Press, 1999)
This text describes principles for understanding and managing permanent neuropsychological impairment in brain-damaged adults. It also presents a new perspective on disorders of self-awareness and recovery, and deterioration after brain injury, which have clear implications for neurorehabilitation.